État actionnaire et capitalisme de connivence au Maroc : le cas de la Caisse de dépôt et de gestion (CDG) - Mohamed Oubenal; Abdellatif Zeroual (Revue de la Régulation)
In this article, we analyse the track record of the Moroccan state-owned institutional investor, the Caisse de dépôt et de gestion (CDG). This enables us to understand the emergence of the “state as shareholder” logic in a context of crony capitalism. The CDG was founded during a developmental era when the state played a central role in the industrialization of the country. Despite the resurgence of developmental aspirations with the Moroccanization policy in the 1970s, the CDG was quickly captured by Moroccan crony capitalism embedded in a hierarchical global economic system. It suffered from the privatizations of the 1990s for the benefit of companies related to the holders of political power.In the 2000s, the organization and strategy of the CDG changed to comply with the constraints/injunctions of a shareholder logic. There was a transformation in the CDG’s executives, with a move from an ethos of state administrators to financial managers seeking to maximize the profitability of their investments. This led to the establishment of active portfolio management as well as the launch of new financial instruments.